2003
DOI: 10.1074/jbc.m309396200
|View full text |Cite
|
Sign up to set email alerts
|

The Redox State of the Cell Regulates the Ligand Binding Affinity of Human Neuroglobin and Cytoglobin

Abstract: Neuroglobin and cytoglobin reversibly bind oxygen in competition with the distal histidine, and the observed oxygen affinity therefore depends on the properties of both ligands. In the absence of an external ligand, the iron atom of these globins is hexacoordinated. There are three cysteine residues in human neuroglobin; those at positions CD7 and D5 are sufficiently close to form an internal disulfide bond. Both cysteine residues in cytoglobin, although localized in other positions than in human neuroglobin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
384
6
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(413 citation statements)
references
References 37 publications
20
384
6
3
Order By: Relevance
“…It has also been shown that the disulfide bond in the CD region can affect the kinetics of hexacoordination by lowering k -H for Ngb (9). Our results suggest that this effect is not the same for Cgb, where an increase in k -H was observed in the presence of DTT.…”
Section: Additional Binding Phases Observed By Flash Photolysismentioning
confidence: 49%
See 1 more Smart Citation
“…It has also been shown that the disulfide bond in the CD region can affect the kinetics of hexacoordination by lowering k -H for Ngb (9). Our results suggest that this effect is not the same for Cgb, where an increase in k -H was observed in the presence of DTT.…”
Section: Additional Binding Phases Observed By Flash Photolysismentioning
confidence: 49%
“…After a treatment of 24 h at 4°C with 10 mM DTT (as described by Hamdane et al (9)), the protein solutions were reacted with 1 mM CO. The resulting time course for Ngb is indeed slower but still exhibits two different phases of binding with nearly equal amplitudes.…”
Section: Co Binding To Maize Hbs (Hbm1 and Hbm2mentioning
confidence: 99%
“…3A). These forms might represent atypical migrations of stable protein conformations and it has been hypothesized that rupture/ formation of the intra molecular (CD7-B5) disulfide bond of NGB [50] can give rise to different apparent molecular mass forms [49]. Posttranslational modifications could also occur, such as covalent links of cofactors or phosphorylation.…”
Section: Expression Of Ngb Ch-iq-ab and Full Length Adgb In Sf9 Cellsmentioning
confidence: 99%
“…These results argue against a role for mammalian Ngbs as an intracellular O 2 store. The lower P 50 value that was originally recorded for human Ngb was presumably due to in vitro formation of an internal disulfide bridge in the protein (20), which increases the affinity for O 2 (see below). We have also shown that, in contrast to Mb, the O 2 affinity of Ngb is markedly sensitive to changes in pH, and that, depending on the temperature range, both normal and reverse Bohr effects are present (indicating an increase or a decrease in the O 2 affinity, respectively, with a pH increase) (19).…”
Section: Neuroglobin As a Promoter Of O 2 Supplymentioning
confidence: 99%
“…A common feature of vertebrate Ngbs is the presence of two to three solvent-accessible reactive cysteine residues (19,20). These are located at the level of the CD corner and D helix (one or two cysteines) or in the G helix (one cysteine) of the protein.…”
Section: Neuroglobin As a Redox Thiol-sensormentioning
confidence: 99%